Enhancing Educational Aspiration of Students and Teachers at SMP Negeri 3 Tegalwaru, Kampung Ilmu - Grashinta, Aully; Baiduri, Intan; Adhilah, Syifa; Prasetyawati, Wuri; Rifameutia, Tjut; Septiana, Eva (Fakultas Psikologi Universitas Pancasila, 2025)
.